Analysis of the Clean Water Distribution Scheme in Tamangil Nuhuten Village, Kei Besar Selatan Sub-District of Southeast Maluku Regency, Using EPANET 2.2 - Rumihin, Paschal; Patriadi, Andi; Sajiyo, Sajiyo (Darul Yasin Al Sys, 2025)
The availability of clean water is a very basic need to support the lives of village communities. Tamangil Nuhuten Village, located in the South Kei Besar area, Southeast Maluku, faces various challenges in the supply and distribution of clean water. This study aims to analyze the clean water distribution scheme in Tamangil Village, Southeast Nuhuten. The results of the study show that the distribution of clean water in Tamangil Nuhuten Village still faces various challenges, especially in terms of accessibility, infrastructure, and meeting the needs of the community. Of the three main springs that are sources of clean water, only Spring A has the highest discharge of 10 liters/second with the closest distance of 1.5 km from settlements. However, only 20% of households have direct access to simple water pipelines, while the other 80% have to transport water manually, with a daily fulfillment rate of only 35%. This condition causes most people, especially those who live far from water sources, to spend more than two hours per day just to get clean water. This inequality of access has an impact on people's quality of life, including an increased risk of waterborne diseases. Data shows a 15% increase in diarrhoea cases during the dry season due to the use of water from unprotected sources. In addition, the time spent transporting water reduces people's productivity in economic activities and children's education. Limited distribution infrastructure and low community participation in clean water management are the main obstacles in creating an efficient distribution scheme.